How to enhance primary school EFL-teacher curriculum-design competences: the Competence Unit Design Model (CUD Mod) - Capperucci, Davide (Onomázein, 2020)
This paper focuses on the development of curriculum design and methodological competences for pre-service and in-service EFL teachers in primary school, considered as essential aspects of the professionalism of teachers. In line with the national and international literature, it addresses some epistemological and methodological aspects of EFL curriculum design with particular reference to how this is dealt with in the Italian school system, even though most of the reflections and methodological proposals that are here presented could be considered useful for any school system. The paper proposes a competence design model, called CUD Mod, based on the “competence unit” framework, experimented in a variety of action-research projects conducted in Tuscan schools at primary and lower secondary level.